Immune Dysregulation in Vitamin D Deficiency: A Case-Control Analysis of Inflammatory Cytokines and Cardiovascular and renal Implications - Ali Saqlain Haider, Zobia Shakil, Irfana Hassan, Muhammad Ahmad Raza Butt, Nadeem Abbas, Khadija Kiran, Oluwadamilola Onanuga, (International Journal of Pharmacy Research & Technology (IJPRT), 2025)
Deficiency of vitamin D has increasingly been implicated in immune dysregulation and in thepathogenesis of cardiovascular and renal disorders. In this case-control analysis we aimed to investigate the associations